Mass, Measurement, Materials, and More Mathematical Modeling: The Nuts and Bolts of Let’s Make an Error - Scott A Sinex; Theodore L. Chambers; Joshua B. Halpern (Spreadsheets in Education, 2012)
How can you get students into analyzing and understanding errors? A second semester general chemistry experiment is presented that introduces students to error analysis via simple mass determinations using nuts, bolts, and washers. Students work in groups of four, each group having a triple beam pan balance. The three-hour laboratory consists of four parts: calibrating the balance using standard masses; making errors to discover the behavior of constant and proportional systematic errors via data analysis in Excel; analyzing the effects of an errant nut in a sequential addition of nuts to a bolt, graphical analysis, and sharing data in Google Docs (now Google Drive) for a collaborative online discussion by groups using the chat function, and finally a verification of the errant nut problem by simulation of results in an interactive animated spreadsheet. Each group has a different set of results and must figure out what is possibly wrong with their results using online chat. Students must use some algebraic detective work to find the outlier (the errant nut), and its influence on the regression line. Students are exposed to linear regression in first semester general chemistry.